Case report: Hemorrhagic fever with renal syndrome presenting as hemophagocytic lymphohistiocytosis - De Smet, Maarten A. J.; Bogaert, Simon; Schauwvlieghe, Alexander; Dendooven, Amélie; Depuydt, Pieter; Druwé, Patrick (Frontiers in Medicine, 2022)
Hemophagocytic lymphohistiocytosis may occur in patients with genetic predisposition and in sporadic cases due to malignancy or infection. We describe a 49-year old man with hemorrhagic fever, type 1 respiratory insufficiency and acute kidney injury. Diagnostic work up showed a hyperinflammatory syndrome, hypertriglyceridemia, hemophagocytosis, very high ferritin and significantly elevated sCD25. The findings were compatible with hemophagocytic lymphohistiocytosis based on the HLH-2004 criteria. Serological testing indentified Puumala virus as the causal pathogen. The patient was successfully treated with pulse corticosteroids, intravenous immunoglobins and supportive therapy.